Clinical practice guidelines for the perioperative nutritional, metabolic, and nonsurgical support of the bariatric surgery patient—2013 update: Cosponsored by american association of clinical endocrinologists, The obesity society, and american society for metabolic & bariatric surgery*123. (26th March 2013) - Mechanick, Jeffrey I.; Youdim, Adrienne; Jones, Daniel B.; Garvey, W. Timothy; Hurley, Daniel L.; McMahon, M. Molly; Heinberg, Leslie J.; Kushner, Robert; Adams, Ted D.; Shikora, Scott; Dixon, John B.; Brethauer, Stacy
Abstract: Abstract: The development of these updated guidelines was commissioned by the AACE, TOS, and ASMBS Board of Directors and adheres to the AACE 2010 protocol for standardized production of clinical practice guidelines (CPG). Each recommendation was re‐evaluated and updated based on the evidence and subjective factors per protocol. Examples of expanded topics in this update include: the roles of sleeve gastrectomy, bariatric surgery in patients with type‐2 diabetes, bariatric surgery for patients with mild obesity, copper deficiency, informed consent, and behavioral issues. There are 74 recommendations (of which 56 are revised and 2 are new) in this 2013 update, compared with 164 original recommendations in 2008. There are 403 citations, of which 33 (8.2%) are EL 1, 131 (32.5%) are EL 2, 170 (42.2%) are EL 3, and 69 (17.1%) are EL 4. There is a relatively high proportion (40.4%) of strong (EL 1 and 2) studies, compared with only 16.5% in the 2008 AACE‐TOS‐ASMBS CPG. These updated guidelines reflect recent additions to the evidence base. Bariatric surgery remains a safe and effective intervention for select patients with obesity. A team approach to perioperative care is mandatory with special attention to nutritional and metabolic issues.